Diagnostic value of neutrophil-lymphocyte ratio in preeclampsia: A PRISMA-compliant systematic review and meta-analysis - Zheng, Wen-Fei (Medicine (Baltimore), 2019)
BACKGROUND: Neutrophil-lymphocyte ratio (NLR) is one of the markers of systemic inflammation. Recent studies have associated NLR with diagnosis of preeclampsia (PE). However, due to small sample sizes and different research design, the diagnostic value of NLR in PE patients is not well understood. In this study, we evaluate the potential diagnostic value of NLR in PE. METHODS: We searched PubMed, Embase, Cochrane Library, the Chinese National Knowledge Infrastructure (CNKI) databases, Wanfang data, VIP database and China Biomedical Literature Database systematically for relevant literatures up to May 20, 2018. All analyses were conducted using Meta-DiSc1.4 and Stata 12.0 software. Sensitivity, specificity and other measures of accuracy of NLR for the diagnosis of PE were pooled. Meta-regression was performed to identify the sources of heterogeneity. RESULTS: This meta-analysis included a total of 7 studies. The pooled sensitivity and specificity were 0.74 (95% CI 0.71–0.76) and 0.64 (95%CI 0.61–0.68), positive likelihood ratio, 2.62 (95%CI1.79–3.84); negative likelihood ratio, 0.34 (95%CI 0.24–0.48); diagnostic odds ratio, 8.44 (95%CI 4–17.78), and area under the curve was 0.82. Meta regression showed that sample size was the main source of heterogeneity. Deeks funnel plot showed that there was no statistical significance for the evaluation of publication bias (P = .16). CONCLUSION: Current evidence suggests that the diagnostic accuracy of NLR has unsatisfactory specificity but acceptable sensitivity for diagnosis of PE. Further large-scale prospective studies are required to validate the potential applicability of using NLR alone or in combination other markers as PE diagnostic biomarker and explore potential factors that may influence the accuracy of NLR for PE diagnosis.